Energy Flow Analysis of One-Dimensional Structures with Random Properties - Kun Wang; Yu Fu; Jiafu Liu; Qi Zhang (Shock and Vibration)
In this work, the energy density responses of one-dimensional structures with random properties are investigated analytically. Based on Green kernels, analytical representations of energy density for vibrating rods and beams are proposed using the superposition of energy waves. Considering random properties in rods and beams, formulations of energy density responses are obtained. Then, the mathematical expectations and variances are derived. And response intervals for random responses are developed. Finally, numerical simulations are performed to validate the proposed formulations, and characteristics of the random energy density responses of rods and beams are analysed. The main contribution of this work is that a new approach to energy density responses is proposed which facilitates the vibration analysis of structures with uncertainty parameters.